Pengembangan prototipe dan analisis ekonomi mesin ekstraksi pati sagu tipe pengaduk berulir yang dilengkapi unit pemarut - Homer, Ian Imanuel; Darma, Darma; Santoso, Budi (Program Pascasarjana Universitas Papua, 2025)
ABSTRACT: Sago is a staple food especially for Papuans. To process sago, the pith crushing and extraction process is very time-consuming and labor-intensive. The purpose of this research is to develop a threaded stirrer type sago starch extraction machine equipped with a grater unit. This research consists of three stages, namely (1) machine development, (2) machine testing and (3) economic feasibility analysis. The research method used was an experimental method using a completely randomized design consisting of three treatments of the type of grater cylinder, namely (1) 4 mm iron axle 20 mm high (P1), circular saw cutting edge (P2) and chain saw serrations (P3). The performance of each treatment was evaluated by measuring variables (1) processing capacity, (2) starch yield, (3) starch production, (4) loss of starch left in the pulp and (5) gasoline fuel consumption. Based on the results of the research, it shows that the threaded stirrer type sago starch extraction machine equipped with a grating unit from the development works well in field conditions. The results of the performance test in field conditions showed that the treatment of the type of grater serrations gave no significant effect on processing capacity, starch yield, starch production, starch loss in dregs and gasoline fuel consumption. The performance of the machine under field conditions (operational) was (1) processing capacity ranged from 255.63 kg/hour - 296.61 kg/hour. (2) starch yield 23.41%. - 30.41%, (3) starch production of 59.94 kg/hour - 90.57 kg/hour, (4) starch loss in pulp of 2.20% - 2.94% and (5) gasoline fuel consumption of 1.30 l/hour - 1.42 l/hour. Economically, this machine is categorized as feasible with a BC ratio value of 2.11. The production break-even point is 3,453 kg and the price break-even point is Rp. 5,487.